STIGMA DAN RESILIENSI ANAK LUAR NIKAH: ANALISIS NARATIF MEDIA SOSIAL BERBASIS MODEL TODOROV DAN PERSPEKTIF MAQĀṢID AL-SYARĪ‘AH - Ridwan; Muhsan (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This research aims to explore the transformation of identity and resilience of children born out of wedlock amid social stigma through the perspective of Islamic law and Maqāṣid al-Syarī‘ah. Using a qualitative method with a Mixed Deductive-Inductive Narrative Analysis approach, this study dissects ten authentic narratives from the Quora digital platform using Tzvetan Todorov's five-stage structural framework. The results show that the transformation of the subjects' identities moves consistently from a state of assumed normality towards a new equilibrium marked by residual trauma due to collective stigma. A disconnect was found between protective normative legal texts and a sociological reality that tends to be discriminatory. The stigma of being an “illegitimate child” and misconceptions about lineage law trigger self-stigma that hinders the subject's access to civil rights. As a solution, this study formulates a resilience model that integrates the reconstruction of a legal paradigm based on jalb al-maṣāliḥ, empathetic administrative reform of law enforcement institutions, and the strengthening of a social support system based on fiṭrah values. The study concludes that protecting the dignity of children born out of wedlock within the framework of Maqāṣid al-Syarī‘ah must go beyond biological certainty towards substantive justice that guarantees the well-being, honor, and social rights of children without discrimination.